Training of Improving Students’ Speaking Skills by Using Talking Ball Game at SMA Kalam Kudus Medan. - Erika Sinambela; Carolina Pakpahan; Poster Sagala (English Lecturers and Teachers Association (ELTA), 2022)
Speaking requires someone to be linguistically competent in terms of well articulating the sound, having sufficient vocabulary, and mastering structural and or grammatical grammar. Speaking is complex because speakers are involved in a rapid and dynamic process incurring a high element of doing various things at the same time. Games are a structured form of play, usually undertaken for enjoyment and sometimes used as an educational tool. Games are distinct from work, which is usually carried out for remuneration, and from art, which is more often an expression of aesthetic or ideological elements. In Talking Ball Game, students can value ability speaking like pronunciation, vocabulary, fluency, grammar, and able to make students fun in the games. It is very important for students. In games, students have the opportunity to use the language after learning new vocabulary. And Talking Ball Game is also able to improve the situation in class. In the teaching and learning process, the students took participation when implementing TBG in learning by speaking. Keywords: Students’ Speaking Skill, Talking Ball Game